(untitled) (Dermatology Reports, 2021)
The acronym PHACES stands for posterior fossa malformations, hemangiomas, arterial anomalies (cardiovascular or cerebrovascular), coarctation of the aorta/cardiac defects, eye abnormalities, and sternal defects. The characteristic dermatological clinical manifestation of PHACES syndrome is a segmental and extensive hemangioma, usually on the face. A combined therapy with 1,064 nm Nd-YAG/595-nm pulsed dye laser was performed in a young 15-year-old patient with PHACES syndrome, who presented a hemangioma on the left side of the face, located in the periorbital region. A first session with Nd-YAG laser (2,5 mm spot size, fluence 100 J/cm2, pulse duration 7 ms) for the treatment of teleangectasias and subsequently, three treatment sessions with pulsed dye laser (12 mm spot size, fluence 7 J/cm2, pulse duration 0,5 ms, repetition rate 0,6 Hz), once every 2 months, were performed. No postoperative complications were recorded, except for transient purpura after the pulsed dye laser sessions. The vascular lesion had a decrease in size bigger than 75%, and these results was maintained 6 months after the last treatment. Combined therapy Nd- YAG/pulsed dye laser is an effective and noninvasive procedure for hemangiomas in patients with PHACES syndrome.